Characteristics of Facial Asymmetry in Congenital Superior Oblique Palsy according to Trochlear Nerve Absence - Hee Kyung Yang; Sumin Jung; Taeg Keun WhangBo; Jeong-Min Hwang (Journal of Ophthalmology)
Background/Aims. Facial asymmetry is affected by various developmental factors, and congenital superior oblique palsy (SOP) is one of the most common causes of asymmetric development of the face. The presence of facial symmetry is usually assessed subjectively, which varies with the examiner. We aimed to objectively assess facial asymmetry in patients with unilateral congenital SOP according to the presence or absence of the trochlear nerve on high-resolution magnetic resonance imaging (MRI). Methods. A total of 287 consecutive patients diagnosed with congenital SOP and 82 control subjects were included. Congenital SOP patients were grouped according to the presence (present group) or absence (absent group) of the trochlear nerve using thin-section high-resolution MRI of cranial nerves. We developed a computer-aided detection (CAD) system that could automatically analyze objective indices of facial asymmetry using frontal face photographs. Results. Of the 287 patients with congenital SOP, 60% of patients had ipsilateral trochlear nerve absence and superior oblique muscle (SO) hypoplasia (absent group), while the remaining 40% had a normal SO and trochlear nerve (present group). All but one objective indices related to facial asymmetry were significantly different between congenital SOP patients and controls (all P<0.05). Among these features, the angle of nose deviation was significantly larger in the absent group compared to the present group (P<0.001). Conclusion. Objective analysis of facial asymmetry using our novel CAD system was useful for identifying distinct features of congenital SOP. Deviation of the nose was more prominent in congenital SOP patients with trochlear nerve absence.